Respuesta :

Answer:

[tex]x=3\\y=6[/tex]

Step-by-step explanation:

[tex]x=y-3\\2x+y=12[/tex]

We have already defined that x = y - 3, replace x for this value.

[tex]2x+y=12\\2(y-3)+y=12[/tex]

Distribute 2.

[tex]2y-6+y=12[/tex]

Add 6.

[tex]2y+y=12+6[/tex]

Combine like terms;

[tex]3y=18[/tex]

Divide by 3.

[tex]y=\frac{18}{3}\\ y=6[/tex]

After having found a variable value, in this case y, replace it in the other equation; x = y - 3, to find x.

[tex]x=y-3\\x=6-3\\x=3[/tex]

ACCESS MORE